Electrically Reconfigurable Microwave Metasurfaces With Active Lumped Elements: A Mini Review - Shao, Linda; Zhu, Weiren (Frontiers in Materials, 2021)
Metasurfaces, a kind of two-dimensional artificially engineered surfaces consist of subwavelength unit cells, have recently attracted tremendous attention, owing to their exotic abilities for tailoring electromagnetic responses. With active lump elements incorporated into the design of metasurfaces, dynamic reconfigurabilities enabled by external stimuli could be realized, offering opportunities for the dynamic manipulation of electromagnetic waves. In this mini review, we present a brief review on the recent progress of electrically reconfigurable metasurfaces at microwave frequencies. A brief discussion will also be given with our outlook on future development direction and possible challenges in this interesting field.